Quantitative Measurement of Plasma Free Metanephrines by a Simple and Cost-Effective Microextraction Packed Sorbent with Porous Graphitic Carbon and Liquid Chromatography-Tandem Mass Spectrometry - Xin Xiong; Yuanyuan Zhang; Rongsheng Zhao (Journal of Analytical Methods in Chemistry)
Plasma free metanephrines are widely used for the diagnosis of pheochromocytoma and paraganglioma (PPGL), yet quantifying metanephrines using a simple and cost-effective approach may be challenging due to preanalytical and analytical constraints. In this study, we established and validated a new method for quantitative measurement of plasma free metanephrines based on microextraction by packed sorbent (MEPS) with porous graphitic carbon (PGC) and liquid chromatography-tandem mass spectrometry (HILIC-MS/MS). The elution step was fully compatible with HILIC mode without evaporation and reconstitution. The analytes were well resolved, and potential interferences (54 substances) were investigated. This method was linear from 24.7–2717 pg/mL for metanephrine (MN) and 24.5–4010 pg/mL for normetanephrine (NMN) with a coefficient of determination (R2) higher than 0.994. The limit of MN and NMN detection were 12.4 pg/mL and 12.3 pg/mL, respectively. The intra- and interassay impressions were ≤12.8% for spiked quality controls and ≤13.6% for commercial quality controls; the method recoveries ranged within 88.0–109.0%, respectively. The area under the receiver operating characteristic (ROC) curve was 0.848 ± 0.047 for MN and 0.979 ± 0.021 for NMN. Validation that was performed by comparing clinical specimens with various biochemical results showed that plasma free metanephrines in a seated position had comparable sensitivity and lower specificity to urinary free metanephrines, which could be compensated by combining other biochemical tests. The newly developed MEPS method resulted as a time-saving, reliable, and cost-effective microextraction technique that can be applied for a successful screening of PPGL.